Carbon Sequestration by the Standing Mangrove Trees at the Achara Estuary along the Coast of Maharashtra State (India) - Kulkarni, N A (Plantae Scientia, 2021)
Mangroves or all the plants are known to absorb the atmospheric carbon by photosynthesis. This absorbed carbon is stored in various organic forms and helps to produce the biomass. Trees dominate this process. Greater and taller is the size of the tree more is the amount of carbon fixed. Hence trees are the major plant forms to absorb maximum atmospheric carbon and biomass production. Thus, the present investigation was carried out to calculate the carbon sequestration of 12 standing mangrove tree species in Achara estuary of Sindhudurg district of Maharashtra state. The biomass and total organic carbon of standing trees is estimated by the non-destructive method. The population of Avicennia marina var. acutissima Staf. & Mold. and Rhizophora mucronata Lamk. are more in the estuary and they sequestrate about 585.70×106 and 375.10×106 lbs carbon respectively. A total of 1892.96×106 lbs of the carbon is sequestering by all the mangrove trees present in the estuary.